Analisis Diagnostik Kesulitan Belajar Mahasiswa PGSD Pada Mata Kuliah Konsep Dasar Matematika II - Alyusfitri, Rieke; Wahyuni, Yusri (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
This study aims to describe the learning difficulties of PGSD students in Basic Mathematics Concept II lecture which is viewed from the location, type and factor of student learning difficulties. From the results of research conducted obtained: 1.The location of learning difficulties of students in learning materials data processing on the subject of Basic Mathematics Concept II is on the indicator: determine the mean, median, and mode for single data with 75.478 percentage, 2. the types of learning difficulties experienced by students in the subject matter of the basic concept of mathematics II are the types of procedural and skill errors with each percentage of 27% and 20%. Therefore, it is important for students to understand and master the concept of the material and understand the procedures (skills) done in solving a problem.